Understanding intention to use communication technology among legislators: a UTAUT model perspective - Hafiar, Hanny; Sjoraida, Diah Fatma; Amin, Kholidil (Faculty of Communications Science, Dr. Soetomo University, 2022)
During the Covid-19 pandemic, face-to-face meetings are restricted; therefore, communication technology such as video conferencing apps is essential for workers, including legislators. Using the Unified Theory of Acceptance and Use of Technology (UTAUT), this study examines technology acceptance factors on the intention to use video conferencing apps by legislators of the West Java Provincial House of Representatives during the COVID-19 pandemic. The respondents of this study were 92 legislators who were chosen randomly. The results showed that the technology acceptance factors were associated with the intention, even simultaneously predicting the intention to use video conferencing apps. There are theoretical and practical implications discussed in the findings of this study. The present study strengthens that the technology acceptance factor in the UTAUT model can explain the mechanism for the emergence of individual intentions. It is necessary to have good social influence and environmental conditions to facilitate individuals in raising behavioural intention to use communication technology.